ANALISIS TINGKAT KEPUASAN PASIEN TERHADAP PELAYANAN PERCUTANEOUS CORONARY INTERVENTION DAN ANGIOGRAFI DI RUANGAN CATH-LAB MURNI TEGUH MEMORIAL HOSPITAL - Akti Ancha; Dior Manta Tambunan (Indonesian Trust Nursing Journal, 2023)
Health services in hospitals as the front line play a very high role in the satisfaction received by patients, as well as PCI and angiography services. The level of satisfaction can be identified based on the dimensions of tangible, responsiveness, reliability, assurance, and empathy. The purpose of this study is to analyze the level of patient satisfaction with PCI and angiography services. This research method is quantitative research with a descriptive design using a cross sectional approach. The research was conducted in the Murni Teguh Memorial Hospital Cath-Lab Room. Total population of 162 patients and samples were 62 respondents using accidental sampling technique. The data used are primary data and secondary data. The analysis was carried out in a univariate manner presented in the frequency distribution table. This study shows that patient satisfaction based on tangible (physical evidence) of PCI and Angiography services in the Murni Teguh Memorial Hospital Cath-Lab unit is mostly in the satisfied category (56.5%), based on responsiveness (responsiveness) the category feels satisfied (67.7%), based on reliability in the satisfied category (69.4%), based on assurance in the satisfied category (64.5%), based on empathy in the satisfied category (58.1 %). Overall, the level of patient satisfaction with PCI and Angiography services in the Murni Teguh Memorial Hospital Cath-Lab Room, the majority were satisfied (85.5%), a small portion were quite satisfied (14.5%). It is concluded that patients are satisfied with PCI and angiography services in the Murni Teguh Memorial Hospital Cathlab Room based on tangible, responsiveness, reliability, assurance, and empathy. It is recommended for future researchers to add variables to the factors related to the level of patient satisfaction with nurse services. Abstrak Pelayanan kesehatan di rumah sakit sebagai lini terdepan berperan sangat tinggi atas kepuasan yang diterima oleh pasien, demikian juga pada pelayanan PCI dan angiografi. Tingkat kepuasan dapat diidentifikasi berdasarkan dimensi tangible, responsiveness, reliability, assurance, dan empathy. Penelitian ini bertujuan untuk menganalisis tingkat kepuasan pasien terhadap pelayanan PCI dan angiografi. Metode penelitian ini adalah penelitian kuantitatif dengan desain deskriptif menggunakan pendekatan Cross Sectional. Penelitian dilakukan di Ruangan Cathlab Murni Teguh Memorial Hospital. Jumlah populasi sebanyak 162 pasien dan sampel diperoleh sebanyak 62 orang. Penarikan sampel secara accidental sampling. Data yang digunakan data primer dan data sekunder. Analisis dilakukan secara univariat yang disajikan dalam tabel distribusi frekuensi. Hasil penelitian ini menunjukkan bahwa kepuasan pasien berdasarkan tangible (bukti fisik) terhadap pelayanan PCI dan Angiografi di Ruangan Cath-Lab Murni Teguh Memorial Hospital sebagian besar pada kategori merasa puas (56,5%), berdasarkan responsiveness (daya tanggap) kategori merasa puas (67,7%), berdasarkan reliability (kehandalan) pada kategori puas (69,4%), berdasarkan assurance (jaminan) pada kategori merasa puas (64,5%), berdasarkan empathy (empati) kategori merasa puas (58,1%). Secara keseluruhan, tingkat kepuasan pasien terhadap pelayanan PCI dan Angiografi di Ruangan Cath-Lab Murni Teguh Memorial Hospital, sebagian besar merasa puas (85,5%), sebagian kecil cukup puas (14,5%). Maka dapat disimpulkan bahwa pasien puas terhadap pelayanan PCI dan angiografi di Ruangan Cathlab Murni Teguh Memorial Hospital berdasarkan tangible, responsiveness, reliability, assurance, dan empathy. Maka disarankan kepada peneliti selanjutnya untuk menambahkan variabel faktor-faktor yang berhubungan dengan tingkat kepuasan pasien terhadap pelayanan perawat di Ruangan Cathlab Murni Teguh Memorial Hospital